The Impact of Rewards on Employee Motivation in SME in Klang Valley, Malaysia - Yang, Yu (2014)
In the economy of Malaysia, Small and Medium Enterprise (SMEs) play an important role that is considered as the backbone of the economy. Small and Medium Enterprise (SMEs) make so many contributions to development of economy by virtue of their contribution to Gross Domestic Product and employment rate in Malaysia. The importance of employee motivation, affecting the behaviors of small and medium enterprises’ employees to behave in right ways, can ultimately decide the failure and success of each small and medium enterprise. Therefore, it is important that managers of SMEs motivate their employees in their organizations. In developing economies like Malaysia, the lack of motivation among employees to improve productivity is due to their not having goal-oriented reward system. Thus, the objective of this study is to try to examine the relationship between rewards and employees motivation in SMEs in Klang Valley. In addition, quantitative method will be used while 200 questionnaires will be distributed to the employees who are my respondents in SMEs. The employees are of individuals that are above 18 years old who had worked in SME for more than six months. The data will be analyzed using SPSS (Statistical Product and Service Solutions) software version 20.